Relationships between Fitness Status and Blood Biomarkers in Professional Soccer Players. (11th April 2022) - Silva, Ana Filipa; González-Fernández, Francisco Tomás; Ceylan, Halil Ibrahim; Silva, Rui; Younesi, Saeid; Chen, Yung-Sheng; Badicu, Georgian; Wolański, Paweł; Murawska-Ciałowicz, Eugenia; Clemente, Filipe Manuel
Abstract : Background . Physical conditions are recognized to be optimal after the pre-season (PS) phase in professional sports. Given that blood measures may also reveal variations, which in turn, may present associations with fitness changes. Objective . The aim of this study is to test the changes of blood markers and physical fitness outcomes at the beginning and following the PS phase. Additionally, we aimed also to analyze the associations of training adaptations between blood markers and the physical fitness measures. Methodology . 25 professional male soccer players (28.1 ± 4.6 years old, 2.0 ± 7.8 kg, and 176.7 ± 4.9 cm) were assessed for hematological and biochemical parameters, and physical fitness measures in the baseline and after the phase of PS. Results . Increases in platelets were observed after the PS phase ( p = 0.001, η 2 = 0.39). Regarding the biochemical parameters, significant increases between PS were found for creatinine (Cre) ( p = 0.001, η 2 = 0.66), alkaline phosphatase (ALP) ( p = 0.001, η 2 = 0.79), C-Reactive Protein (CRP) ( p = 0.001, η 2 = 0.74), cortisol (C) ( p = 0.001, η 2 = 0.63), and testosterone ( T ) ( p = 0.001, η 2 = 0.76), whereas significant decreases were found for albumin (Alb) ( p = 0.004, η 2 = 0.29), and calcium corrected (Ca Corr.) ( p = 0.002, η 2 = 0.32). Moderate correlations were found between albumin and the 5-meter linear sprint split ( r = –0.44 (95%CI: –0.71; –0.05)) and CRP ( r = –0.48 (95%CI: –0.74; –0.10)). Moderate correlations were found between VAMEVAL and hemoglobin ( r = 0.44 (95%CI: 0.05; 0.71)). Conclusions . The overall physical fitness measures improved after the PS phase. Also, significant variations (decreases/increases) were observed for the case of biomchemical and hematological outcomes. Coaches should carefully consider the adaptative changes observed in blood parameters as the changes in whole organism and metabolism after specific critical phases as the PS in professional players. Thus, optimal management of stimulus/recovery can be warranted to minimize illness and injury rate and to follow the direction and dynamics of adaptative changes.